Vertical distribution of road traffic noise - MAKAREWICZ, R.; GOŁĘBIEWSKI, R. (Archives of Acoustics, 1998)
Road noise generated by freely flowing traffic is assessed by the time-average sound level, LAT. The noise interaction with the ground surface is the only wave phenomenon that modifies geometrical spreading. A simplified model of the ground effect is applied. The model is founded on the Weyl-Van der Pol solution. Prediction of the time-average sound level, at a perpendicular distance less than 100m and an altitude not exceeding a few tens of meters, requires two simultaneous measurements of LAT at the site of interest.